Corpo-devir: multiplicidade de linguagens na poética em fotografia e vídeo - Santos, Walesca Timmen (2018)
This dissertation deals with a practical and theoretical investigation through a poetic that transits between the languages of photography and video. In the work we try to relate the modus operandi of this process, with the purpose of reflecting on the unfolding of the visuality of the body. The research cut is linked to the concepts of body-becoming and multiplicity that are thought in relation to the performances performed by three actors on the stage of a theater. Issues related to body work, video and photo captions accompany the key concepts in their configurations and construction possibilities, for a contemporary artistic production contributing in the field of culture.